2017
DOI: 10.1021/acs.nanolett.7b03606
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Structure of Electrochemically Deposited Lithium Metal and Its Solid Electrolyte Interphases via Cryogenic TEM

Abstract: Lithium metal has been considered the "holy grail" anode material for rechargeable batteries despite the fact that its dendritic growth and low Coulombic efficiency (CE) have crippled its practical use for decades. Its high chemical reactivity and low stability make it difficult to explore the intrinsic chemical and physical properties of the electrochemically deposited lithium (EDLi) and its accompanying solid electrolyte interphase (SEI). To prevent the dendritic growth and enhance the electrochemical revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
313
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(327 citation statements)
references
References 43 publications
13
313
1
Order By: Relevance
“…After cycling, there are a lot of CO 3 2− (289.5 eV)36, 40 and CF 3 (293.1 eV)38, 39 groups (Figure 5c) on the surface of Li metal anode because of the decomposition of carbonate solvents and Li salt anions. Seen from the F 1s spectra (Figure 5b), the LiF (684.9 eV) and Li x PO y F z (687.4 eV)41, 42 can be observed during the SEI formation, which are the decomposition products of Li salt anions. After cycling, the amount of LiF and Li x PO y F z change significantly and a lot of CF 3 (689.1 eV) groups emerge (Figure 5d), indicating the decomposition of LiTFSI and LiPF 6 during the cycling 38, 43.…”
mentioning
confidence: 99%
“…After cycling, there are a lot of CO 3 2− (289.5 eV)36, 40 and CF 3 (293.1 eV)38, 39 groups (Figure 5c) on the surface of Li metal anode because of the decomposition of carbonate solvents and Li salt anions. Seen from the F 1s spectra (Figure 5b), the LiF (684.9 eV) and Li x PO y F z (687.4 eV)41, 42 can be observed during the SEI formation, which are the decomposition products of Li salt anions. After cycling, the amount of LiF and Li x PO y F z change significantly and a lot of CF 3 (689.1 eV) groups emerge (Figure 5d), indicating the decomposition of LiTFSI and LiPF 6 during the cycling 38, 43.…”
mentioning
confidence: 99%
“…Such technique opens a new window for the atomic-scale investigation of the environment-sensitive materials, which is promising to see novel details that might fail to be unraveled by conventional TEM and will certainly boost the related research in materials science. Right after the publication of Cui's work in Science, a similar study of investigating lithium battery using cryo-TEM was reported, where the authors observed amorphous electrochemically deposited lithium and crystalline LiF [11]. As this is a new direction, more and more attention will definitely be attracted to make use of such a powerful technique in materials science to verify its scope of application and in the meantime to address some critical issues, such as, (1) is any phase change involved during the sample freezing for the inorganic materials?…”
Section: Yong Wangmentioning
confidence: 87%
“…[67,68] Their decomposition products, LiF and organic fluoride, have positive impacts on the electrochemical performance of batteries by forming a stable and compact SEI layer on both the cathode and the anode. [69][70][71][72] Read et al presented a high-voltage electrolyte based on a fluorocarbonate solvent and additive, 1.7 M LiPF 6 in FEC-EMC (4 : 6 w/w) + 5 mM HFIP (tris (hexafluoro-iso-propyl)phosphate), for a dualgraphite battery, which supported the intercalation of PF 6 À at 5.2 V and demonstrated a capacity of 65 mAh g À 1 with an average CE of 97.5 %. [73] In the work of Aladinli et al, the Li/ graphite cell utilizing 0.5 M NaPF 6 /PC electrolyte with 2 vol.% FEC additive exhibited substantially enhanced CEs of > 98 % ( Figure 4).…”
Section: Liu Et Al Investigated the Interactions Between Pfmentioning
confidence: 99%